Larvae of stingless bee Scaptotrigona bipunctata exposed to organophosphorus pesticide develop into lighter, smaller and deformed adult workers - Dorneles, Andressa Linhares; Rosa-Fontana, Annelise De Souza [UNESP]; Santos, Charles Fernando dos; Blochtein, Betina (Elsevier B.V., 2021)
Organophosphorus pesticides such as chlorpyrifos are often used in agriculture due to their broad spectrum of action. However, this insecticide and acaricide is considered highly toxic to the environment and can cause toxicity in nontarget insects such as bees. In addition to adult individuals, immature can also be exposed to residues of this insecticide by larval food. Thus, we investigated the effects of chlorpyrifos concentrations on the larval development of stingless bee Scaptotrigona bipunctata workers reared in vitro. We evaluated four different biomarkers: a) survival, b) development time, c) body mass and d) morphological characteristics (head width, intertegular distance, wing area and proportion of deformed bees). The exposure of the larvae to different doses of chlorpyrifos significantly reduced survival probability but did not cause changes in the development time. Regarding morphometric analysis, bees exposed to chlorpyrifos showed a reduction in body mass and size, and 28% of the emerged adults showed a reduction in wing area and deformations. Therefore, this work shows that S. bipunctata larvae exposed to the sublethal effects of chlorpyrifos are likely to have reduced chances of survival. However, if they emerge, they will be lighter, smaller and less able than equivalent but not exposed workers. These impaired attributes have the potential to compromise the future workforce in colonies exposed to this pesticide. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Chlorpyrifos; Sublethal effects; In vitro rearing; Wing area; Flight range